2020
DOI: 10.14309/ajg.0000000000000545
|View full text |Cite
|
Sign up to set email alerts
|

Health-Related Quality of Life: A Rapid Predictor of Hospitalization in Patients With Cirrhosis

Abstract: OBJECTIVES: Patients with cirrhosis experience a worsened quality of life; this may be quantified by the use of health-related QoL (HRQoL) constructs, such as the chronic liver disease questionnaire (CLDQ) and EuroQoL Group—visual analog scale (EQ-VAS). In this multicenter prospective study, we aimed to evaluate HRQoL as a predictor of unplanned hospital admission/early mortality, identify HRQoL domains most affected in cirrhosis, and identify predictors of low HRQoL in patients with cirrhosis. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
32
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 50 publications
3
32
0
Order By: Relevance
“…CLDQ has been used as a predictor of HRQOL in patients with cirrhosis (35). Consistent with published work from Kok et al (36), in the current series, CLDQ was also found to be an independent predictor of all-cause unplanned hospitalization and deaths. Although uncommonly evaluated, this finding highlights the importance of measuring patient-reported outcomes.…”
Section: Discussionsupporting
confidence: 91%
“…CLDQ has been used as a predictor of HRQOL in patients with cirrhosis (35). Consistent with published work from Kok et al (36), in the current series, CLDQ was also found to be an independent predictor of all-cause unplanned hospitalization and deaths. Although uncommonly evaluated, this finding highlights the importance of measuring patient-reported outcomes.…”
Section: Discussionsupporting
confidence: 91%
“…Frailty is defined as the presence of three or more of the following phenotypes: body weight (BW) loss, self-reported exhaustion, skeletal muscle functional decline, slow walking speed (WS), and decreased PA [4,5]. Recently, the concept of frailty has been enlarged to chronic liver diseases (CLDs) as clinical symptoms of impaired global physical function [6][7][8][9][10][11][12][13][14][15]. Tanaka et al reported that frailty, age of 76 years or more, and open surgery were independent adverse predictors associated with loss of independence after surgery in independently living subjects aged 65 years or more undergoing liver surgery [6].…”
Section: Introductionmentioning
confidence: 99%
“…Patients with decompensated liver disease experience a high symptom burden comparable to that of other end‐stage chronic disease and worse than that experienced by those with compensated liver disease 13 . Distressing symptoms drive poor HRQoL, which is associated with increased mortality and hospitalization 2 . Improvements in HRQoL are likely multifactorial and remain a major clinical objective for this cohort who otherwise have limited treatment options.…”
Section: Discussionmentioning
confidence: 99%
“…The COVID‐19 pandemic has created challenges in how healthcare systems provide care for patients with cirrhosis complicated by refractory ascites. The consequences of refractory ascites can include spontaneous bacterial peritonitis, 1 high healthcare resource utilization, and reduced health‐related quality of life 2 . As the most common complication of decompensated cirrhosis, 3,4 ascites necessitates frequent face‐to‐face interactions with the healthcare system through elective large‐volume paracentesis (LVP), emergency department presentations, and acute hospitalization.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation